Horror stories 2 - Tunku Halim (Fixi Novo which is an imprint of Buku Fixi Sdn Bhd, 2016)
These are the stories that were just too nasty to be included in the bestselling first volume of Horror Stories. Written over the span of two decades by Malaysia s most popular scary author Tunku Halim, this collection includes the full novella Juriah s Song as well as the blackly comic play Pig Heart.